Angels' blood eaudiobook - Singh, Nalini (Guild Hunter, 2010)
Vampire hunter Elena Deveraux knows she is the best—but she does not know if even she is good enough for this job. Hired by the dangerously beautiful archangel Raphael, a being so lethal that no mortal wants his attention, Elena knows failure is not an option—even if the task is impossible. Because this time, it's not a wayward vamp she has to track. It's an archangel gone bad. The job will put Elena in the midst of a killing spree like no other—and pull her to the razor's edge of passion. Even if the hunt does not destroy her, succumbing to Raphael's seductive touch just might. For when archangels play, mortals break.